Arun Joshi’s Use of Symbolism in “The Foreigner” - Dr Mohd Shafi Dar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The purpose of this research paper is to analyze how Arun Joshi used symbolism as a technique to express the human predicament. Arun Joshi uses symbols to present the mystery of human existence. A deep study of the novel reveals that the central experience of his fiction is crisis and quest. Dealing with Sindi Oberoi‟s journey from detachment from the world to his involvement in it, the novelist depicts Sindi‟s anguish resulting from his loneliness and rootlessness. It is the good use of symbolism that Joshi succeeded in exploring the predicament of the protagonist struggling to arrive at reality in the midst of utter chaos and meaninglessness of the mind.